Implementasi Perangkat Pembelajaran Kurikulum 2013 - Salim, Salim; Abubakar, Sitti Rahmaniar; Nurhayati, Nurhayati; Saputra, Hendra Nelva (Institut Agama Islam Negeri Kendari, 2021)
The purpose of this mixed methods research is to describe the implementation of the 2013 curriculum learning tools by elementary school teachers, the differences of the curriculum implementation, and to describe what teachers face in implementing it. The results of data analysis indicate that participants implemented the 2013 curriculum well in all school accreditation level. The problems faced by the elementary school teachers are relative to learning resources, limited facilities and infrastructure, and limited opportunities tocontinuing professional development.Keywords: Curriculum implementation; learning tools; elementary school teachers